The benefits and challenges of conducting research in schools using a single case experimental design. Issue 1 (2nd January 2022) - Maydew, Harriet; Atkinson, Sarah
ABSTRACT: As scientist practitioners, educational psychologists (EPs) are equipped with the necessary research skills to evaluate both the impact of their involvement and the effectiveness of interventions in schools. An increasing area of priority within schools is supporting young people with social, emotional and mental health (SEMH) needs. This paper explores the use of single case experimental designs (SCEDs) as a methodology which can be used to evaluate EP involvement within real world practice. To exemplify this, the evaluation of an SEMH intervention delivered by school staff across four different secondary school settings using a SCED is presented. The challenges and benefits of using a SCED as a research methodology are discussed. The authors conclude that SCEDs provide a flexible and practical method which could be used to evaluate the impact of interventions implemented within typical EP practice. An implication of how such implementation research could be shared within the profession is proposed.